Public Perspectives and Practices in Managing Antibiotic Waste: A Concise Survey - Kaur, Prabhjot; Kriplani, Priyanka; Dass, Rameshwar; Kamboj, Sweta; Kamboj, Rohit; Handa, Uditi; Nagpal, Kajal (Anti-Infective Agents, 2026)
IntroductionAn antibiotic is described as a material that is either manufactured or generated by a single microbe and, at low quantities, may either kill or hinder the development of other organisms. They are still used worldwide to treat and prevent illnesses in clinical and veterinary care. The antibiotic waste can include any dosage form that has been used, unused, stored, etc. Antibiotic abuse and improper waste disposal have an impact on both the environment and people.ObjectiveThe understanding of antibiotics, typical waste management techniques, and raising awareness of accessible trash treatment facilities and disposal techniques among the general public in various Yamuna Nagar, Haryana, India, locations formed the basis of this survey.MethodsA comprehensive analysis, including various regions of Yamunanagar (a city in Haryana) is conducted. Quantitative research results from the systematic examination that yielded the numerical data were collected, analyzed, and reported in this study.Results and DiscussionThe current survey highlights the key trends of antibiotics usage, their waste management disposal habits, and awareness among respondents of Yamuna Nagar. Almost 80% of respondents completed their antibiotic course within the last 6 months while 60% have unused medications at home due to non-completion of the course or keeping them for future use. More than 50% shared, or thought of sharing antibiotics with others. Further, only 6.3% of respondents always seek advice from healthcare professionals before taking antibiotics. Only 12%-24.3% reported receiving proper education regarding the storage and disposal of antibiotics from healthcare professionals. 34.3% of respondents have information regarding the disposal of antibiotic waste management. Further data revealed that people have awareness regarding the potential of improper antibiotic waste disposal to the environment but lack knowledge regarding proper disposal techniques. Further, this study also tends to spread awareness of which impact on the environment, different methods of disposal, along with most closest Common Biomedical Waste Treatment Facilities (CBWTFs) were chosen by the respondents.ConclusionDespite having awareness regarding the negative impacts of incorrect antibiotic waste disposal on the environment and public health, the majority of respondents keep them in their homes and dispose in ordinary household trash. There is a lack of appropriate medication disposal practices and attitudes. The majority of respondents agreed that there is a need for greater awareness regarding the safe disposal of medications. Some strategies that have been proposed include training healthcare professionals to advise patients about proper disposal while prescribing, using social media advertisements, utilizing QR codes on medication packaging, labeling medications with instructions on how to dispose of them, etc.
Keywords: public health